Mini Review of RF Magnetron Sputtering for Aluminum Nitride Thin Film Deposition: Scale-Up Challenges and Perspectives - Salsabiila, Natasya; Nayan, Nafarizal; Azman, Zulkifli; Abu Bakar, Ahmad Shuhaimi; Wan Sabli, Sharaifah Kamariah; Adriyanto, Feri (Emerging Advances in Integrated Technology, 2025)
Radio Frequency (RF) magnetron sputtering is a pivotal technique in thin-film deposition, renowned for its versatility and precision in producing high-quality crystalline films. This method excels in delivering uniform film deposition, high reproducibility, and adaptability for both insulating and conductive materials. Among the materials deposited using RF magnetron sputtering, Aluminum Nitride (AlN) has gained attention due to its wide bandgap, high thermal conductivity, and excellent breakdown voltage. Over the years, researchers have successfully deposited c-axis-oriented AlN films with thicknesses ranging from 8 nm to 2.75?µm, typically on small wafers (2–4 inches) at temperatures up to 900?°C. This mini-review explores the fundamentals, working principles, and application of RF magnetron sputtering for AlN thin film deposition. The novelty lies in synthesizing existing literature on RF magnetron sputtering for AlN deposition and systematically linking key sputtering parameters (RF power, working pressure, gas flow ratio, substrate temperature, target-to-substrate distance, and post-annealing) to film properties, while highlighting the challenges of scaling up to larger wafers. These insights offer a practical reference for optimizing AlN deposition at larger scales.